Investigation of ZIP4, ZO-1, and CLAUDIN-1 expression in thyroid tumours by immunohistochemistry and real-time polymerase chain reaction methods - Nacir, Mustafa; İbiloğlu, ibrahim; Alabalık, Ulaş (Polish Journal of Pathology, 2023)
Thyroid neoplasms are the most common endocrine malignancies. ZIP4 is an intramembranous zinc trans membrane protein. Zinc plays a central role in the activation of transcription factors, and zinc transporters. This affects tumour migration, invasion, and cell proliferation. ZO-1 and Claudin-1 are important tight junction proteins whose amounts increase and decrease in various cancers. In this study, we aimed to investigate the expression of ZIP4, ZO-1, and Claudin-1 in thyroid tumours and the relationship of this expression with tumour types and prognostic parameters. ZIP4, ZO-1, and Claudin-1 were studied in all cases by immunohistochemical and Real-Time PCR methods. ZIP4 and Claudin-1 tended to be expressed more in cases with tumours, while ZO-1 in cases with and without tumours. Expression of ZIP4 and Claudin-1 by real-time polymerase chain reaction showed a significant difference between histological subtypes, and this difference was not observed with ZO-1. It was observed that the presence of metastasis increased with the expression of ZIP4 and Claudin-1, and there was no significant change with ZO-1. We think that Claudin-1 and ZIP4 expression can be used as an important marker in terms of showing poor prognosis and susceptibility to metastasis in thyroid tumours, and in developing targeted therapy.